Availability of healthy and unhealthy foods in modern retail outlets located in selected districts of Greater Accra Region, Ghana - Akosua Pokua Adjei; Gideon Senyo Amevinya; Wilhemina Quarpong; Akua Tandoh; Richmond Aryeetey; Michelle Holdsworth; Charles Agyemang; Francis Zotor; Matilda E. Laar; Kobby Mensah; Phyllis Addo; Dennis Laryea; et al. (Frontiers Media S.A., 2022)
BackgroundIntake of unhealthy foods is linked to the onset of obesity and diet-related non-communicable diseases (NCDs). Availability of unhealthy (nutritionally poor) foods can influence preference, purchasing and consumption of such foods. This study determined the healthiness of foods sold at modern retail outlets- supermarkets and mini-marts in the Greater Accra Region of Ghana.MethodsAll modern retail outlets located in six districts of Greater Accra were eligible. Those < 200 m2 of floor area and with permanent structures were categorized as mini-marts; and those ≥200 m2 as supermarkets. Shelf length of all available foods were measured. Healthiness of food was determined using two criteria - the NOVA classification and energy density of foods. Thus, ultra-processed foods or food items with >225 kcal/100 g were classified as unhealthy. The ratio of the area occupied by unhealthy to healthy foods was used to determine the healthiness of modern retail outlets.ResultsOf 67 retail outlets assessed, 86.6% were mini-marts. 85.0% of the total SHELF area was occupied by foods categorized as unhealthy (ranging from 9,262 m2 in Ashiaman Municipality to 41,892 m2 in Accra Metropolis). Refined grains/grain products were the most available, occupying 30.0% of the total food shelf space, followed by sugar-sweetened beverages (20.1% of total shelf space). The least available food group-unprocessed staples, was found in only one high income district, and occupied 0.1% of the total food shelf space. Retail outlets in two districts did not sell fresh fruits or fresh/unsalted canned vegetables. About two-thirds of food products available (n = 3,952) were ultra-processed. Overall, the ratio of ultra-processed-to-unprocessed foods ranged from 3 to 7 with an average (SD) of 5(2). Thus, for every healthy food, there were five ultra-processed ones in the studied retail outlets.ConclusionThis study reveals widespread availability of ultra-processed foods in modern retail outlets within the selected districts. Toward a healthier food retail environment, public health and food regulators, in partnership with other stakeholders need to institute measures that improve availability of healthy foods within supermarkets and mini-marts.